Two Novel Technologies for the Detection of Anti-cardiolipin and Anti β2–Glycoprotein Antibodies in the Real Life: Chemiluminescent in Comparison to the Addressable Laser Bead Immunoassays. (17th February 2020) - Grossi, Valentina; Infantino, Maria; Benucci, Maurizio; Li Gobbi, Francesca; Bandinelli, Francesca; Damiani, Arianna; Bodio, Caterina; Borghi, Maria Orietta; Mahler, Michael; Aure, Mary Ann; Bentow, Chelsea; Manfredi, Mariangela
ABSTRACT: In the present study, we evaluated two novel technologies, the chemiluminescent immunoassay (CIA) QUANTA Flash on BIO-FLASH (Inova Diagnostics, San Diego, CA, USA) and the addressable laser bead immunoassay (ALBIA) on BioPlex™ 2200 (Bio-Rad, Hercules, CA, USA) for the detection of anti-cardiolipin IgG/IgM (aCL) and anti-β2–glycoprotein IgG/IgM (aβ2GPI) antibodies. The study was performed on 134 samples from consecutive patients (59 males and 75 females, mean age 54 ± 10 years) who consulted a rheumatologist because thrombosis and/or pregnancy complications were present or another immunological disease (Sjogren's syndrome, inflammatory arthritis). Fourteen patients of the total fulfilled 25the Sydney criteria for APS and for these patients previous results of aPLs were available. Sera were tested for aCL and aβ2GPI of IgG and IgM isotypes using CIA (BIO-FLASH) and ALBIA (BioPlex™ 2200). Overall agreement between CIA and ALBIA ranged from 88.1% (aCL IgG) to 97.8% (aβ2GPI IgG). Cohen's kappa coefficient ranged from 0.53 to 0.91, implying moderate to almost perfect agreement. Almost perfect agreement was found between BioPlex™ 2200 and BIO-FLASH aβ2GPI IgG and aCL IgM with Cohen's kappa of 0.91 and 0.88, respectively. On the other hand, moderate agreement was found between BioPlex™ 2200 and BIO-FLASH aCL IgG and β2GPI IgM assays with Cohen's kappa of 0.57 and 0.53, respectively. The two novel technologies look promising and comparable but further studies with larger cohorts are needed to contribute to the better understanding of the new aPLs antibodies assays performance.